Performans produksi burung puyuh (Coturnix coturnix japonica) dengan perlakuan tepung limbah penetasan telur puyuh - Lukluil Maknun; Sri Kismiati; Isna Mangisah (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2015)
The research aimed to evaluate the utilization of Japanese quail hatchery waste powder in feed on feed intake, egg production, egg mass and feed conversion ratio. The materials used were 4 weeks old 160 Japanese quails with an average weight of 94.19 ± 7.36 gram. The experiment used a completely randomized design (CRD) with four treatments (0%, 9%, 12%, and 15% of Japanese quail hatchery waste powder in feed) and five replications. Parameters observed were feed intake, egg production, egg mass and feed conversion ratio. The data were analysed using analysis of variance and continued with Duncan's multiple range test 5% level. The results showed that the addition of Japanese quail hatchery powder in feed had a significant effect (P>0.05) on feed intake and egg mass, but not on egg production and feed conversion ratio. The conclusion of this study was Japanese quail hatchery waste could be used on quail’s feed until 15% without changing feed intake, egg production, egg mass and feed conversion ratio. Keywords: Japanese quail hatchery waste, performance production, Japanese quail